Internalization Of Halal and Tayyiban Eating Habits Among Early Childhood Through Free Nutritious Meal (MBG) Program - Ambar Putri Ramadhani; Alfauzan Amin; Moch Iqbal; Asniti Karni (Al-Munawwarah : Jurnal Pendidikan Islam, 2026)
This study was motivated by the importance of fostering halal and tayyib eating habits from early childhood through the Free Nutritious Meal Program (Makan Bergizi Gratis—MBG) as an effort to strengthen Islamic character values among children at RA Gading Cempaka, Bengkulu City. This study aimed to describe the internalization process of halal and tayyib eating habits and identify the supporting and inhibiting factors affecting its implementation. A qualitative case study approach was employed. Data were collected through observations, in-depth interviews, and documentation involving the principal, teachers, the Nutrition Fulfillment Service Unit (SPPG), parents, and students. The findings indicate that the internalization process was carried out through daily religious practices, including praying before and after meals, handwashing, communal eating, and teacher role modeling. The MBG Program reinforced these practices by providing nutritious, hygienic, safe, and halal food. Supporting factors included teacher commitment, parental involvement, SPPG support, and a conducive school environment. The main challenges were inconsistent habituation between home and school, limited teacher understanding of the halal and tayyib concept, the absence of standard operating procedures, limited stakeholder coordination, and children's selective eating behavior. The study concludes that the MBG Program effectively supports the internalization of halal and tayyib eating habits through collaborative efforts among schools, families, and stakeholders.